Frontispiece: Association and Dissociation of Grignard Reagents RMgCl and Their Turbo Variant RMgCl⋅LiCl. Issue 23 (1st June 2016) - Schnegelsberg, Christoph; Bachmann, Sebastian; Kolter, Marlene; Auth, Thomas; John, Michael; Stalke, Dietmar; Koszinowski, Konrad
Abstract : Grignard Reagents Grignard reagents RMgCl and their so‐called turbo variant RMgCl⋅LiCl are of exceptional synthetic utility, but it remains unclear which species these compounds form in solution and, in particular, in which way LiCl exerts its reactivity‐enhancing effect. In their Full Paper onpage 7752 ff., K. Koszinowski et al. report the use of a combination of four techniques to analyze solutions of various RMgCl species in ethereal solvents in the absence and presence of LiCl. Some of the Grignard reagent forms anionic ate complexes in solution, the abundance of which strongly increases upon addition of LiCl, thus rationalizing its beneficial effect on the reactivity.